2021
DOI: 10.1186/s12968-020-00703-2
|View full text |Cite
|
Sign up to set email alerts
|

Fully quantitative mapping of abnormal aortic velocity and wall shear stress direction in patients with bicuspid aortic valves and repaired coarctation using 4D flow cardiovascular magnetic resonance

Abstract: Background Helices and vortices in thoracic aortic blood flow measured with 4D flow cardiovascular magnetic resonance (CMR) have been associated with aortic dilation and aneurysms. Current approaches are semi-quantitative or when fully quantitative based on 2D plane placement. In this study, we present a fully quantitative and three-dimensional approach to map and quantify abnormal velocity and wall shear stress (WSS) at peak systole in patients with a bicuspid aortic valve (BAV) of which 52% h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 44 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…WSS can also be assessed with three-dimensional (3D), time-resolved phase-contrast cardiovascular magnetic resonance (CMR) imaging with three-directional velocity encoding (4D flow CMR), that allows for 3D blood flow quantification in the vasculature throughout the cardiac cycle [ 19 ]. While 4D flow CMR has widely been used to investigate altered WSS in the diseased thoracic aorta [ 20 – 22 ], previous studies of WSS and OSI in patients with AAA are limited. Takehara et al [ 23 ] found reduced peak WSS values and elevated OSI in AAA when compared to non-dilated proximal aortic segments in a cohort of 18 AAA patients.…”
Section: Introductionmentioning
confidence: 99%
“…WSS can also be assessed with three-dimensional (3D), time-resolved phase-contrast cardiovascular magnetic resonance (CMR) imaging with three-directional velocity encoding (4D flow CMR), that allows for 3D blood flow quantification in the vasculature throughout the cardiac cycle [ 19 ]. While 4D flow CMR has widely been used to investigate altered WSS in the diseased thoracic aorta [ 20 – 22 ], previous studies of WSS and OSI in patients with AAA are limited. Takehara et al [ 23 ] found reduced peak WSS values and elevated OSI in AAA when compared to non-dilated proximal aortic segments in a cohort of 18 AAA patients.…”
Section: Introductionmentioning
confidence: 99%
“…3 ) can be explained by the presence of large-scale flow recirculation patterns. 19 , 31 , 46 Such flow features have been associated to (1) intimal lipid accumulation 22 in murine and rabbit thoracic aorta, and (2) atherosclerotic and thrombotic biological markers in an arterial replication platform. 32 As explained in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…6,11,13,23,26 Furthermore, hemodynamic disturbances are intertwined with and exacerbated by concomitant AAo dilation and aortic valve abnormalities, such as bicuspid aortic valve (BAV) or deficient tricuspid aortic valves (TAV). 14,28,36,46 In recent years, 4D flow magnetic resonance imaging (MRI) has been increasingly used to obtain information on both aortic morphology and hemodynamics 5,14,31,35,43 -in particular in the presence of aortic vascular/valve pathologies 4,16,23,31 -providing risk markers of AAo wall degeneration. 14,25,43 With the objective of providing a comprehensive characterization of the spatiotemporal heterogeneity of large-scale aortic flow features and of their possible links with AAo dilation, a recently proposed approach integrating computational hemodynamics with Complex Networks (CNs) theory 7,8,13,37 is here extended for the first time to 4D flow MRI in patients with and without aortic dilation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we present an aortic 4D flow MRI analysis, providing a comprehensive quantification and visualization of abnormal aortic velocity and WSS magnitude and direction with state-of-the-art techniques [15] , [16] in MFS patients. We hypothesize that an abnormal hemodynamic profile could be found in aortic regions which are known predilection sites for aortic dissection (aortic root and proximal descending aorta).…”
Section: Introductionmentioning
confidence: 99%